Dyslexia : A parents' guide to dyslexia, dyspraxia and other learning difficulties - Muter, Valerie; Likierman, Helen (London : Vermilion, 2008)
This is a hands-on guide for parents that will help them to identify and manage their child's learning difficulties.
Includes bibliographical references (p. 231) and index.
Keywords: Dyslexia -- Popular works; Dyslexic children -- Education; Dyslexic children -- Psychology; Dyslexic children -- Family relationships; Parent and child; Education